2015
DOI: 10.1177/0954008315577440
|View full text |Cite
|
Sign up to set email alerts
|

Near superhydrophobic-fluorinated THV fiber-like structures and fibers prepared by electrospinning

Abstract: In the fluoropolymers family, one of the newest members is the terpolymer of tetrafluoroethylene, hexafluoropropylene, and vinylidene fluoride (THV). There are scarce data on THV, and therefore it is necessary to study different properties of THV. In the current research, the detailed surface morphology and water wettability of electrospun microfibers prepared from THV/ethyl acetate solutions in the pure state and with the addition of Wyoming-type low-magnesium montmorillonite are discussed. The morphology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
(81 reference statements)
3
9
1
Order By: Relevance
“…Moreover, in the report by Ok et al (20), Wyoming montmorillonite with low Mg was utilized, and in the present study, Ca-rich Texas montmorillonite has been used. In the study by Ok et al (20), both "fiber-like" structures and "beans"-type fibers were observed, while in the present study, mainly smooth fibers were obtained, which will be discussed later. In the current report, besides measuring the hydrophobicity, oleophilicity of the fibers is also tested.…”
Section: Introductionsupporting
confidence: 47%
See 2 more Smart Citations
“…Moreover, in the report by Ok et al (20), Wyoming montmorillonite with low Mg was utilized, and in the present study, Ca-rich Texas montmorillonite has been used. In the study by Ok et al (20), both "fiber-like" structures and "beans"-type fibers were observed, while in the present study, mainly smooth fibers were obtained, which will be discussed later. In the current report, besides measuring the hydrophobicity, oleophilicity of the fibers is also tested.…”
Section: Introductionsupporting
confidence: 47%
“…Montmorillonite (STx-1b), a Ca 2+ rich clay, was added into the 15 wt% THV/acetone solution with two different weight ratios of polymer:clay (wt:wt/10:1) and (wt:wt/5:1). The amount of montmorillonite to be added into the polymer solution was determined referring to the previous report by Ok et al (20). The polymer-clay solution was mixed thoroughly with a magnetic stirrer bar for 30 min to disperse the clay (till having milky solution due to white color of the clay) into the polymer-solvent mixture before electrospinning the fibers (see Table 1 summarizing the experimental conditions and the corresponding figures of the results).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result indicated that the water contact angles of the lms were as high as 118 and 145 . 22,23 However, the as-prepared lms in these studies were not suitable for MD application due to lack of interconnected pores. To the best of our knowledge, except for the abovementioned two studies, no other studies have been reported on the THV membrane.…”
Section: Introductionmentioning
confidence: 95%
“…Poly(TFE-co-HFP-co-VDF) (THV), a terpolymer of tetra-uoroethylene, hexauoropropylene and vinylidene uoride, possesses outstanding hydrophobicity, chemical resistance, [22][23][24] and mechanical properties 25 and appears to be another excellent uorinated copolymer for membrane fabrication for MD. In previous studies, the fabrication of hydrophobic thin lms through both NIPS and electrospinning methods has been investigated.…”
Section: Introductionmentioning
confidence: 99%